Christus in natura - Kindschi Garský, Zbyněk; Hirsch-Luipold, Rainer (Studies of the Bible and Its Reception (SBR), 2020)
This volume offers detailed studies into the Physiologus, a Greek manuscript probably written in Egypt in the 2nd century CE. The Physiologus was the first Christian text to sum up a general understanding of nature using biblical and pagan sources and it has an extensive reception history throughout the medieval period. Its symbolic use of animals and plants, etc., has deeply influenced visual arts, literature, and heraldry, but this visual language often remains enigmatic. This book, going back to a project of the Swiss National Foundation (Das ‹Evangelium der Natur›. Der griechische Physiologus und die Wurzeln der frühchristlichen Naturdeutung) offers new insights into the origins and the interpretation of this symbolic language.